Construction Project Sustainability: The Role of Contractor Practices in Waste Management - ASYRAF,; Yusof, Yusmarwati; Ibrahim Mukhtar, Marina; Roddin, Rohayu (Research and Innovation in Technical and Vocational Education and Training, 2024)
The construction industry is a sector that contributes significantly to the economy in Malaysia. However, this rapid development brought in a large amount of construction waste and the contractor needs knowledge on how the construction waste should be managed strategically while the sustainability of the construction project could be maintained. A quantitative approach using survey design is adopted in this study. The questionnaire as a study instrument and software used to make descriptive and inferential analysis is the Statistical Package for Social Science (SPSS) version 29. The findings showed that under the Solid Waste Management and Cleansing Regulations, the majority of respondents ensure that construction waste is handled by a competent or licensed party. On the part of construction waste management methods, the majority of respondents ensure that construction waste is disposed of only in gazette areas. Furthermore, the majority of respondents believe that recycling construction trash can enhance cost-effective advantages to a project, and that there is a strong correlation between knowledge, the sustainability of construction projects and construction waste management techniques. Consequently, there is difference between construction waste management practices on the sustainability of construction projects based on the G1, G4 and G7 contractor classes. Therefore, this study is important in assisting Johor State contractors in managing construction waste more effectively and consistently in the future so that the sustainability element can be applied in construction projects in Malaysia.